The complete mitochondrial genome of blue-crowned laughingthrush Pterorhinus courtoisi (Ménégaux, 1923), a critically endangered species endemic to China - Lei Chen; Mengyao Sun; Zenghao Gao; Di Xu; Weiwei Zhang (All Life, 2023)
The blue-crowned laughingthrush Pterorhinus courtoisi (Ménégaux, 1923) is listed as a critically endangered species on the International Union for Conservation of Nature Red List. This species occupies an extremely small known breeding range in China. In this study, we obtain the complete mitochondrial genome of the blue-crowned laughingthrush by using Illumina NovaSeq sequencing. The total length of the genome is 17,875 bp, containing 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes and 2 control regions, with a slight A-T preference (52.84%) in base composition.